P77 Health-related quality of life and functional outcomes following curative treatments for rectal cancer: A population-level study in England. (13th September 2016) - Downing, A; Finan, PJ; Sebag-Montefiore, D; Wright, P; Thomas, JD; Gilbert, A; Corner, J; Richards, M; Morris, EJA; Glaser, AW
Abstract : Background: Colorectal cancer survival rates continue to improve and the use of multimodal therapy including radiotherapy is now common. Consequently, there is a growing population of survivors at risk of morbidity secondary to treatment. In January 2013, all individuals still alive 12–36 months post-diagnosis of colorectal cancer in England were sent a survey. This study focuses on the rectal cancer survivors and investigates how curative treatments for rectal cancer influence health-related quality of life (HRQL) and functional outcomes. Methods: The survey response data were linked to data from the National Cancer Data Repository, a resource containing detailed information about the care of all individuals with cancer in England. The generic HRQL (EQ-5D) and cancer-specific outcomes (FACT and Social Difficulties Inventory items) related to bowel, urinary and sexual function were analysed in relation to type of surgery and receipt of radiotherapy and/or chemotherapy. Results: Questionnaires were returned by 6, 713 (64.2%) of 10, 452 eligible patients of whom 4, 453 were in remission after a major resection and 3, 988 formed the final sample for analysis. Overall, 32.9% of respondents reported 'perfect' HRQL (no problems) whilst 67.1% reported ≥1 HRQL problem (on any EQ-5D domain). Individuals with a stoma still present were more likely to report ≥1 HRQL problem than those without a stoma (74.6% compared to 61.7%, p < 0.001). Respondents who had radiotherapy and/or chemotherapy were more likely to report ≥1 HRQL problem than those who did not. Respondents who had radiotherapy reported lower levels of bowel control: 24.8% reported good control compared to 41.6% in the no radiotherapy group (p < 0.001). Urinary dysfunction and sexual difficulties were consistently higher for those with a stoma present. For sexual difficulties, receipt of radiotherapy resulted in a higher level of difficulties (33.5% answered Quite a bit/Very much compared to 18.9% in those who did not receive radiotherapy, p < 0.001). Those undergoing a stoma reversal reported better outcomes than those with a stoma still present. Conclusion: A large population based cross sectional assessment of HRQL is feasible. This study is the largest to date. A stoma-forming operation (which is not or cannot be subsequently reversed) and the use of radiotherapy are associated with worse reported outcomes. This study supports the reversal of stomas, where possible, and a selective approach to the use of radiotherapy in treating rectal cancer. Linkage studies of HRQL with other routinely collected treatment information are needed to improve the balance between treatment efficacy and toxicity.